Sulfate-resistant concrete

By using a combination technology of modified carbon nanotubes and plugged tube fibers in concrete, the problem of concrete being susceptible to corrosion when exposed to sulfate environment is solved, and the effect of improving the durability and sulfate corrosion resistance of concrete is achieved.

CN116253538BActive Publication Date: 2025-03-07SICHUAN JINGYIDA ENG INSPECTION CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310295845.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-24
Publication Date
2025-03-07
Estimated Expiration
2043-03-24

AI Technical Summary

Technical Problem

Concrete is susceptible to sulfate erosion when exposed to saline soil and seawater, resulting in reduced durability and structural safety risks.

Method used

Using the combined technology of modified carbon nanotubes and plugged tube fibers, the modified carbon nanotubes are successively coated with an oxide metal layer and a soluble sulfate adsorption layer on the inner wall of the carbon nanotube. The plugged tube fibers are used to seal the ports of the modified carbon nanotubes to form a material system that can adsorb and fix sulfate ions.

Benefits of technology

It effectively avoids the migration of sulfate ions to the inside of the concrete, reduces the erosion of sulfate ions on the concrete, and improves the durability and sulfate corrosion resistance of the concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116253538B_ABST
    Figure CN116253538B_ABST
Patent Text Reader

Abstract

The present application relates to the field of concrete, and specifically discloses a concrete resistant to sulfate erosion and a preparation method thereof. A concrete resistant to sulfate erosion, the raw materials of which include cement, fly ash, slag powder, sand, gravel, water, admixture, modified carbon nanotubes and tube-blocking fibers; the modified carbon nanotubes are obtained by sequentially coating an oxide metal layer and a soluble sulfate adsorption layer on the inner wall of the carbon nanotubes; the tube-blocking fibers are used to block the ports of the modified carbon nanotubes. The preparation method thereof is as follows: Step 1: Mix cement, fly ash, slag powder, sand, gravel and modified carbon nanotubes to obtain a dry premix; Step 2: Mix water, admixture, tube-blocking fibers and dry premix, and stir to obtain concrete resistant to sulfate erosion. The concrete of the present application can be used for deep-sea tunnel casting projects or saline land construction projects, and has excellent resistance to sulfate erosion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of concrete, and more particularly, to concrete resistant to sulfate attack. Background Art

[0002] Concrete is usually made of cement as the binder, sand and stone as aggregates, and water with admixtures and additives in a certain proportion and mixed to obtain cement concrete. It has the advantages of easy molding, low energy consumption, good durability, low price, and can be combined with steel to make various load-bearing structures. It is the main material of modern engineering structures. At this time, the durability of concrete is directly related to the service life of the concrete structure.

[0003] Sulfate erosion of concrete is a very harmful type of erosion and damage, and is also one of the important factors affecting the durability of concrete. For example, there is a large area of ​​saline land in northwest my country, and the seawater in coastal areas is rich in sulfate. Concrete buried underground for a long time in contact with saline soil and seawater will be damaged by sulfate, a corrosive medium in saline soil and seawater, which seriously endangers the service life of concrete and poses a safety hazard to the building structure. Therefore, the research and development of sulfate-resistant concrete has great practical value. Summary of the invention

[0004] In order to resist sulfate corrosion on concrete, the present application provides concrete that is resistant to sulfate corrosion.

[0005] In a first aspect, the present application provides a concrete resistant to sulfate erosion, which adopts the following technical solution: The concrete resistant to sulfate erosion is characterized by comprising the following raw materials in parts by weight:

[0006] 250-300 parts of cement;

[0007] 40-60 parts of fly ash;

[0008] 50-70 parts of slag powder;

[0009] 600-700 parts of sand

[0010] 800-850 parts of crushed stone;

[0011] 220-250 parts of water;

[0012] 6-8 parts of admixture;

[0013] 40-80 parts of modified carbon nanotubes;

[0014] 40-60 parts of pipe plugging fiber;

[0015] The modified carbon nanotube is obtained by coating an oxide metal layer and a soluble sulfate adsorption layer on the inner wall of the carbon nanotube in sequence; the plugging fiber is used to plug the port of the modified carbon nanotube.

[0016] By adopting the above technical scheme, a part of cement is replaced by an appropriate amount of fly ash and slag, thereby reducing the amount of cement used. While ensuring the performance of concrete, the physical and chemical reaction between sulfate ions and silicates in cement can be reduced, thereby reducing the expansive chemical corrosion caused by the reaction between sulfate ions and silicates.

[0017] By adding modified carbon nanotubes, after the sulfate adsorption layer in the modified carbon nanotubes is soaked in the infiltrated seawater for a long time, the soluble sulfate adsorption layer dissolves and falls off, and the fallen adsorption layer can adsorb sulfate ions that penetrate into the concrete into the modified carbon nanotubes. At the same time, after the sulfate adsorption layer falls off, the oxidized metal layer is exposed, and then the sulfate ions adsorbed into the modified carbon nanotubes react with the oxidized metal layer to generate sulfate crystals, which are attached to the inner wall of the modified carbon nanotubes, thereby fixing the sulfate ions and preventing the sulfate ions from migrating and diffusing into the concrete; when the sulfate crystals are formed, as time goes by, the sulfate crystals in the modified carbon nanotubes grow freely, so that the inner wall of the modified carbon nanotubes forms an uneven wall surface, and the uneven wall surface has a reinforcing effect on the sulfate crystals formed later. On the one hand, it improves the bonding force between the sulfate crystals formed later and the wall surface, and on the other hand, the uneven wall surface can hinder the sulfate crystals detached from the carbon nanotubes from migrating out of the modified carbon nanotubes, thereby preventing the sulfate ions from migrating and diffusing into the concrete.

[0018] By adding tube-blocking fibers, the tube-blocking fibers can reduce the tensile stress in the concrete, thereby achieving the effect of organizing the generation and development of concrete cracks; the added tube-blocking fibers are randomly distributed at the ports of the modified carbon nanotubes, and the tube-blocking fibers located at the ports of the modified carbon nanotubes will not affect the liberation of sulfate ions into the modified carbon nanotubes, but when the sulfate ions form sulfate crystals with the metal oxide layer, the tube-blocking fibers located at the ports of the modified carbon nanotubes can prevent the sulfate crystals from falling off from the modified carbon nanotubes and migrating to the outside of the modified carbon nanotubes, and can achieve the blocking of the ports of the modified carbon nanotubes, thereby further enhancing the fixation effect of sulfate ions.

[0019] The concrete of the present application adsorbs and fixes sulfate ions through modified nanotubes, and then further reinforces the sulfate ions through tube-blocking fibers, effectively avoiding the problem of sulfate ions easily migrating into the interior of the concrete, thereby reducing the corrosion of sulfate ions on the concrete and further improving the durability of the concrete.

[0020] Optionally, the metal oxide layer includes any one of a zirconium oxide layer, a nickel oxide layer and a titanium oxide layer.

[0021] By adopting the above technical solution, the above-mentioned metal oxide layer can form zirconium sulfate, nickel sulfate and titanium sulfate respectively with sulfate ions. The above-mentioned three sulfate crystals have a faster growth rate, so that the sulfate ions can be quickly fixed, thereby reducing the residence time of sulfate ions in the concrete system, and further reducing the corrosion of sulfate ions to concrete.

[0022] Optionally, the sulfate adsorption layer is a chitosan layer.

[0023] By adopting the above technical solution, the chitosan layer is hydrolyzed after being immersed in seawater that penetrates into the concrete to form a large number of chitosan macromolecules. Since the chitosan macromolecules contain a large number of active hydroxyl and amino groups, they have a strong adsorption and migration guiding effect on sulfate ions, which is conducive to fully adsorbing sulfate ions into the modified carbon nanotubes.

[0024] Optionally, the tube-blocking fiber includes any one of polypropylene fiber and polyamide fiber.

[0025] By adopting the above technical scheme, the organic groups at the ends of the polypropylene fibers and polyamide fibers have good bonding force with the graphite of the modified carbon nanotubes, which is conducive to the aggregation of the tube-blocking fibers at the ports of the modified carbon nanotubes, and further conducive to achieving the effect of blocking the ports of the modified carbon nanotubes.

[0026] Optionally, the modified carbon nanotubes are obtained by a preparation method comprising the following steps:

[0027] S1: Anhydrous ethanol and a hydrogen peroxide solution with a mass concentration of 32-35% are mixed in a mass ratio of 1:1 to obtain a treatment solution, an oxidized metal powder is added to the treatment solution to obtain an anhydrous ethanol-hydrogen peroxide-oxidized metal mixed solution, carbon nanotubes are added to the anhydrous ethanol-hydrogen peroxide-oxidized metal mixed solution, and then ultrasonic, centrifugal, and drying treatments are performed to separate the pre-branched carbon nanotubes;

[0028] S2: The pre-branched carbon nanotubes obtained in S1 are immersed in a chitosan aqueous solution, and the modified carbon nanotubes are obtained after magnetic stirring, centrifugation and drying.

[0029] By adopting the above technical scheme, the thickness of the metal oxide layer and the sulfate adsorption layer on the inner wall of the modified carbon nanotube prepared by the above method is uniform, and the metal oxide layer and the sulfate adsorption layer can be stably attached to the inner wall of the modified carbon nanotube after centrifugal treatment, thereby effectively improving the structural stability of the modified carbon nanotube, which is beneficial to prevent the metal oxide layer and the sulfate adsorption layer from falling off during the preparation of concrete.

[0030] Optionally, the thickness of the metal oxide layer is 3-5 nanometers, and the thickness of the sulfate adsorption layer is 1-2 nanometers.

[0031] By adopting the above technical solution, selecting the thickness of the sulfate adsorption layer to be 1-2 nanometers is conducive to the rapid dissolution of the sulfate adsorption layer after contact with seawater, thereby quickly adsorbing sulfate ions in seawater into the modified carbon nanotubes, and is conducive to exposing the metal oxide layer. Selecting the thickness of the metal oxide layer to be 3-5 nanometers is conducive to the metal oxide layer to play its role in fixing sulfate ions for a long time, thereby enabling the concrete to maintain long-term resistance to sulfate corrosion.

[0032] Optionally, the mass ratio of the metal oxide powder to the treatment liquid in S1 is 1:(3-5).

[0033] By adopting the above technical scheme, the above ratio of metal oxide powder and treatment liquid is conducive to uniformly dispersing the metal oxide powder in the treatment liquid, thereby forming a uniform anhydrous ethanol-hydrogen peroxide-metal oxide mixture, which is conducive to forming a metal oxide layer with stable composition on the inner wall of the carbon nanotube.

[0034] In a second aspect, the present application provides a method for preparing a method for preparing concrete resistant to sulfate corrosion, using the following technical solution:

[0035] A method for preparing concrete resistant to sulfate corrosion comprises the following steps:

[0036] Step 1: Mix cement, fly ash, slag powder, sand, crushed stone and modified carbon nanotubes, and stir for 60-90 seconds to obtain a dry premix;

[0037] Step 1: Mix water, admixture, pipe plugging fiber and dry premix, and stir for 2-3 minutes to obtain concrete that is resistant to sulfate attack.

[0038] By adopting the above technical scheme, the process for preparing concrete resistant to sulfate erosion is simple and easy to operate. The working performance of the prepared concrete meets the construction requirements, and the concrete is not easily corroded by sulfate and has good corrosion resistance and durability.

[0039] In summary, this application has the following beneficial effects:

[0040] 1. Since the present application adopts modified carbon nanotubes and tube-plugging fibers, the sulfate ions are adsorbed and fixed by the modified nanotubes, and then the sulfate ions are further reinforced by the tube-plugging fibers, which effectively avoids the problem of sulfate ions easily migrating into the interior of the concrete, thereby reducing the corrosion of sulfate ions on the concrete, and then improving the durability of the concrete.

[0041] 2. In the present application, zirconium oxide layer, nickel oxide layer and titanium oxide layer are preferably used as the metal oxide layer. Since the above three sulfate crystals have a faster growth rate, the sulfate ions can be quickly fixed, thereby reducing the residence time of the sulfate ions in the concrete system, thereby reducing the corrosion of the sulfate ions on the concrete.

[0042] 3. The present application adopts polypropylene fiber or polyamide fiber as the tube-blocking fiber. The organic groups at the ends of the polypropylene fiber and the polyamide fiber have good bonding force with the graphite of the modified carbon nanotube, which is conducive to the aggregation of the tube-blocking fiber at the port of the modified carbon nanotube, and then is conducive to achieving the effect of blocking the port of the modified carbon nanotube, thereby preventing sulfate crystals from falling off from the modified carbon nanotube and migrating to the outside of the modified carbon nanotube, and further enhancing the fixation effect of sulfate ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 is a schematic diagram of the end face structure of the modified carbon nanotubes prepared in Preparation Example 3 of the present application;

[0044] Figure 2 It is a schematic diagram of the end face structure of the modified carbon nanotubes prepared in Preparation Example 7 of the present application.

[0045] Figure numerals: 1, carbon nanotube; 2, metal oxide layer; 3, sulfate adsorption layer. DETAILED DESCRIPTION

[0046] The present application is further described in detail below in conjunction with embodiments.

[0047] The experimental raw materials used in the preparation examples and embodiments of this application are all commercially available.

[0048] Preparation example of modified carbon nanotubes

[0049] Preparation Example 1

[0050] A modified carbon nanotube is prepared by the following steps:

[0051] S1: 10 kg of anhydrous ethanol with a mass concentration of 32% and 10 kg of hydrogen peroxide with a mass concentration of 15% are mixed to obtain a treatment liquid, 6.6 kg of zirconium oxide powder is added to the treatment liquid, and stirred for 20 minutes to obtain an anhydrous ethanol-hydrogen peroxide-zirconium oxide mixed liquid, 10 kg of carbon nanotubes are added to the mixed liquid, and then ultrasonically treated for 15 minutes, and then centrifuged for 15 minutes, and then the carbon nanotubes are fished out from the mixed liquid, and then dried to obtain pre-branched carbon nanotubes;

[0052] S2: The obtained pre-branched carbon nanotubes are immersed in a chitosan aqueous solution with a molar concentration of 75%, and subjected to magnetic stirring for 10 minutes, followed by centrifugal treatment for 10 minutes. The pre-branched carbon nanotubes are then removed from the chitosan aqueous solution and dried to obtain modified carbon nanotubes.

[0053] Preparation Example 2

[0054] A modified carbon nanotube is prepared by the following steps:

[0055] S1: 10 kg of anhydrous ethanol with a mass concentration of 34% and 10 kg of hydrogen peroxide with a mass concentration of 15% are mixed to obtain a treatment liquid, 5.0 kg of nickel oxide powder is added to the treatment liquid, and stirred for 20 minutes to obtain an anhydrous ethanol-hydrogen peroxide-nickel oxide mixed liquid, 10 kg of carbon nanotubes are added to the mixed liquid, and then ultrasonically treated for 25 minutes, and then centrifuged for 25 minutes, and then the carbon nanotubes are fished out from the mixed liquid, and then dried to obtain pre-branched carbon nanotubes;

[0056] S2: The obtained pre-branched carbon nanotubes are immersed in a chitosan aqueous solution with a molar concentration of 75%, and subjected to magnetic stirring for 15 minutes, followed by centrifugal treatment for 15 minutes. The pre-branched carbon nanotubes are then removed from the chitosan aqueous solution and dried to obtain modified carbon nanotubes.

[0057] Preparation Example 3

[0058] A modified carbon nanotube is prepared by the following steps:

[0059] S1: 10 kg of anhydrous ethanol with a mass concentration of 35% and 10 kg of hydrogen peroxide with a mass concentration of 15% are mixed to obtain a treatment liquid, 4.0 kg of titanium oxide powder is added to the treatment liquid, and stirred for 20 minutes to obtain an anhydrous ethanol-hydrogen peroxide-titanium oxide mixed liquid, 10 kg of carbon nanotubes are added to the mixed liquid, and then ultrasonically treated for 35 minutes, and then centrifuged for 35 minutes, and then the carbon nanotubes are fished out from the mixed liquid, and then dried to obtain pre-branched carbon nanotubes;

[0060] S2: The obtained pre-branched carbon nanotubes are immersed in a chitosan aqueous solution with a molar concentration of 75%, and subjected to magnetic stirring for 20 minutes, followed by centrifugal treatment for 20 minutes. The pre-branched carbon nanotubes are then removed from the chitosan aqueous solution and dried to obtain modified carbon nanotubes.

[0061] Preparation Example 4

[0062] A modified carbon nanotube is prepared by the following steps:

[0063] S1: 10 kg of carbon nanotubes were immersed in a chitosan aqueous solution with a molar concentration of 75%, and magnetically stirred for 20 minutes, and then centrifuged for 20 minutes. The pre-branched carbon nanotubes were then fished out of the chitosan aqueous solution and dried to obtain modified carbon nanotubes.

[0064] Preparation Example 5

[0065] A modified carbon nanotube is prepared by the following steps:

[0066] S1: 10 kg of anhydrous ethanol with a mass concentration of 35% and 10 kg of hydrogen peroxide with a mass concentration of 15% are mixed to obtain a treatment liquid, 4.0 kg of titanium oxide powder is added to the treatment liquid, and stirred for 20 minutes to obtain an anhydrous ethanol-hydrogen peroxide-titanium oxide mixed liquid, 10 kg of carbon nanotubes are added to the mixed liquid, and then ultrasonically treated for 35 minutes, and then centrifuged for 35 minutes, and then the carbon nanotubes are fished out of the mixed liquid, and then dried to obtain modified carbon nanotubes.

[0067] Preparation Example 6

[0068] A modified carbon nanotube is different from Preparation Example 3 in that the metal oxide powder in step S1 is copper oxide powder.

[0069] Preparation Example 7

[0070] A modified carbon nanotube, which is different from Preparation Example 3 in that S2 is:

[0071] S2: The obtained pre-branched carbon nanotubes are immersed in a chitosan aqueous solution with a molar concentration of 75%, and subjected to magnetic stirring for 40 minutes, followed by centrifugal treatment for 40 minutes. The pre-branched carbon nanotubes are then removed from the chitosan aqueous solution and dried to obtain modified carbon nanotubes.

[0072] Example

[0073] Example 1

[0074] A concrete resistant to sulfate attack, wherein the components and their corresponding weights are shown in Table 1, and the preparation steps are as follows: Step 1: Mix cement, fly ash, slag powder, sand, crushed stone and modified carbon nanotubes, and stir for 60 seconds to obtain a dry premix;

[0075] Step 1: Mix water, admixture, pipe plugging fiber and dry premix, and stir for 2 minutes to obtain concrete resistant to sulfate attack.

[0076] The modified carbon nanotubes are the modified carbon nanotubes prepared in Preparation Example 1; the tube-blocking fibers are polypropylene fibers; and the additive is a polycarboxylic acid high-efficiency water-reducing agent.

[0077] Example 2

[0078] A concrete resistant to sulfate attack, wherein the components and their corresponding weights are shown in Table 1, and the preparation steps are as follows: Step 1: Mix cement, fly ash, slag powder, sand, crushed stone and modified carbon nanotubes, and stir for 80 seconds to obtain a dry premix;

[0079] Step 1: Mix water, admixture, pipe plugging fiber and dry premix, and stir for 2.5 minutes to obtain concrete resistant to sulfate attack.

[0080] The modified carbon nanotubes are the modified carbon nanotubes prepared in Preparation Example 2; the tube-blocking fibers are polypropylene fibers; and the additive is a polycarboxylic acid high-efficiency water-reducing agent.

[0081] Example 3

[0082] A concrete resistant to sulfate attack, wherein the components and their corresponding weights are shown in Table 1, and the preparation steps are as follows: Step 1: Mix cement, fly ash, slag powder, sand, crushed stone and modified carbon nanotubes, and stir for 90 seconds to obtain a dry premix;

[0083] Step 1: Mix water, admixture, pipe plugging fiber and dry premix, and stir for 3 minutes to obtain concrete resistant to sulfate attack.

[0084] The modified carbon nanotubes are the modified carbon nanotubes prepared in Preparation Example 3; the tube-blocking fibers are polyamide fibers; and the additive is a polycarboxylic acid high-efficiency water-reducing agent.

[0085] Table 1 Weight of each raw material in Examples 1-3 (kg)

[0086] Raw material name Example 1 Example 2 Example 3 cement 25 27 30 Fly ash 4 5 6 Slag powder 5 6 7 Sand 60 65 70 gravel 80 83 85 water 22 23 25 Admixtures 0.6 0.7 0.8 Modified carbon nanotubes 4 6 8 Pipe plugging fiber 4 5 6

[0087] Example 4

[0088] A concrete resistant to sulfate corrosion, which is different from Example 3 in that the modified carbon nanotubes are the modified carbon nanotubes prepared in Preparation Example 4.

[0089] Example 5

[0090] A concrete resistant to sulfate corrosion, which is different from Example 3 in that the modified carbon nanotubes are the modified carbon nanotubes prepared in Preparation Example 5.

[0091] Example 6

[0092] A concrete resistant to sulfate corrosion, which is different from Example 3 in that the modified carbon nanotubes are the modified carbon nanotubes prepared in Preparation Example 6.

[0093] Example 7

[0094] A concrete resistant to sulfate corrosion, which is different from Example 3 in that the modified carbon nanotubes are the modified carbon nanotubes prepared in Preparation Example 7.

[0095] Example 8

[0096] A concrete resistant to sulfate corrosion, which is different from Example 3 in that the pipe-plugging fibers are steel fibers.

[0097] Comparative Example

[0098] Comparative Example 1

[0099] A concrete resistant to sulfate corrosion, which is different from Example 3 in that an equal amount of sand is used to replace the modified carbon nanotubes.

[0100] Comparative Example 2

[0101] A concrete resistant to sulfate corrosion, which is different from Example 3 in that an equal amount of unmodified carbon nanotubes is used to replace the modified carbon nanotubes.

[0102] Comparative Example 3

[0103] A concrete resistant to sulfate attack, which is different from Example 3 in that no polyamide fiber is added.

[0104] Performance testing

[0105] According to the sulfate corrosion resistance test method in GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the corrosion resistance, compressive strength and flexural strength of the concrete in Examples 1-8 and Comparative Examples 1-3 were tested. The test results are shown in Table 2.

[0106] Table 2 Performance test results

[0107] project Erosion times / times Corrosion resistance coefficient / % Compressive strength / MPa Flexural strength / MPa Example 1 150 96.7 55.6 5.9 Example 2 150 97.4 57.5 6.1 Example 3 150 98.3 58.7 6.2 Example 4 150 67.3 35.6 4.2 Example 5 150 61.2 31.5 3.9 Example 6 150 82.3 43.6 4.8 Example 7 150 90.2 50.2 5.1 Example 8 150 87.6 47.4 5.0 Comparative Example 1 150 33.6 25.6 2.9 Comparative Example 2 150 35.7 26.8 3.0 Comparative Example 3 150 83.6 45.9 4.9

[0108] From Examples 1-3, Comparative Example 1 and Table 2, it can be seen that the corrosion resistance coefficient, compressive strength after corrosion and flexural strength of the concrete prepared in Examples 1-3 of the present application are better than those of the concrete prepared in Comparative Example 1, indicating that the mutual compatibility between the raw material formulas of the concrete of the present application is scientific and reasonable, and can effectively improve the sulfate corrosion resistance and durability of the concrete, especially the modified carbon nanotubes have a key role in improving the sulfate corrosion resistance of the concrete.

[0109] Combining Examples 3-5 and Table 2, it can be seen that the corrosion resistance coefficient, compressive strength after corrosion and flexural strength of the concrete obtained in Examples 4 and 5 are all lower than those in Example 3, indicating that the modified carbon nanotubes prepared by the modification method of the present application have a good effect on improving the resistance of concrete to sulfate corrosion. Since the modified carbon nanotubes used in Example 4 only have a sulfate adsorption layer composed of chitosan, but no oxidized metal layer, after the sulfate adsorption layer adsorbs the sulfate ions in the concrete system into the carbon nanotubes, the sulfate ions are still in a free state, so there are still some sulfate ions that diffuse and migrate into the interior of the concrete, thus causing the concrete to be corroded. However, the modified carbon nanotubes used in Example 5 only have an oxidized metal layer, but no sulfate adsorption layer, and the sulfate ions cannot be directed to gather in the carbon nanotubes, and thus cannot be adsorbed and fixed with the oxidized metal layer, thus causing the concrete to be corroded by sulfate.

[0110] Combining Example 3, Example 6 and Table 2, it can be seen that the corrosion resistance coefficient, compressive strength and flexural strength of the concrete prepared in Example 6 are all lower than those in Example 3. Since the oxide metal layer in the modified carbon nanotubes uses copper oxide, and the growth rate of copper oxide crystals is very slow, it is impossible to quickly fix the sulfate ions in the carbon nanotubes. Therefore, most of the sulfate ions still diffuse and migrate into the concrete, resulting in the corrosion of the concrete, which in turn leads to a decrease in the compressive strength and flexural strength of the concrete.

[0111] Combining Example 3, Example 7 and Table 2, it can be seen that the corrosion resistance coefficient, compressive strength after corrosion and flexural strength of the concrete prepared in Example 7 are all lower than those in Example 3. Since the magnetic stirring and centrifugation time of the modified carbon nanotubes used in Example 7 are too long in the S2 step during the preparation, which leads to a thicker sulfate adsorption layer, the dissolution rate of the sulfate adsorption layer is slow, and the sulfate ions adsorbed into the carbon nanotubes are freed to the outside of the carbon nanotubes before they have time to contact the oxidized metal layer. Therefore, the sulfate ions continue to diffuse and migrate into the interior of the concrete, thereby causing the concrete to be corroded.

[0112] Reference Figure 1 In Preparation Example 3, after magnetic stirring for 20 minutes and centrifugal treatment for 20 minutes in S2, the thickness of the formed sulfate adsorption layer 3 is about 2 nanometers; Figure 2 In Preparation Example 7, after S2 was magnetically stirred for 40 minutes and centrifuged for 40 minutes, the thickness of the formed sulfate adsorption layer 3 reached 10-12 nanometers, thereby hindering the exposure of the oxide metal layer 2, resulting in the inability to fix the sulfate ions.

[0113] Combining Example 3, Example 8 and Table 2, it can be seen that the corrosion resistance coefficient, compressive strength after corrosion and flexural strength of the concrete prepared in Example 8 are all lower than those in Example 3. Since steel fibers are used and the bonding force between the steel fibers and the graphite of the modified carbon nanotubes is weak, the steel fibers cannot gather at the ports of the modified carbon nanotubes, thereby failing to seal the ports of the modified carbon nanotubes. Therefore, when sulfate ions and the oxidized metal layer form sulfate crystals, the detached sulfate crystals migrate to the outside of the modified carbon nanotubes, thereby corroding the concrete.

[0114] From Example 3, Comparative Example 1 and Comparative Example 2 and Table 2, it can be seen that the corrosion resistance coefficient, compressive strength after corrosion and flexural strength of the concrete prepared in Comparative Example 1 and Comparative Example 2 are all lower than those in Example 3, indicating that the use of unmodified carbon nanotubes does not have a significant enhancing effect on the sulfate corrosion resistance of concrete, and the data of Comparative Example 1 and Comparative Example 2 are relatively close, indicating that the effects of using unmodified carbon nanotubes and not adding modified carbon nanotubes are basically the same, and both cannot improve the sulfate corrosion resistance of concrete.

[0115] Combining Example 3, Comparative Example 3 and Table 2, it can be seen that the corrosion resistance coefficient, compressive strength after corrosion and flexural strength of the concrete prepared in Comparative Example 3 are all lower than those in Example 3, indicating that the sulfate corrosion resistance of the concrete will be significantly reduced when the plugging fiber is not used. The reason may be the same as the reason why the corrosion resistance of the concrete is reduced by using steel fiber in Example 8. Therefore, using plugging fiber to block the ports of the modified carbon nanotubes plays an important role in improving the sulfate corrosion resistance of the concrete.

[0116] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A sulfate-resistant concrete, characterized in that: The raw materials include the following parts by weight: 250-300 parts of cement; 40-60 parts of fly ash; 50-70 parts of slag powder; 600-700 parts of sand; 800-850 parts of crushed stone; Water 220-250 parts; admixture 6-8 parts; 40-80 parts of modified carbon nanotubes; 40-60 parts of pipe plugging fiber; The modified carbon nanotubes are obtained by sequentially coating an oxide metal layer and a chitosan layer on the inner wall of the carbon nanotubes; The thickness of the metal oxide layer is 3-5 nanometers, and the thickness of the chitosan layer is 1-2 nanometers; The metal oxide layer includes any one of a zirconium oxide layer, a nickel oxide layer and a titanium oxide layer; The pipe-blocking fiber is a polyamide fiber; The tube-blocking fiber is used to block the ports of the modified carbon nanotubes.

2. The sulfate-resistant concrete according to claim 1, characterized in that: The modified carbon nanotubes are obtained by a preparation method comprising the following steps: S1: Anhydrous ethanol and a hydrogen peroxide solution with a mass concentration of 32-35% are mixed in a mass ratio of 1:1 to obtain a treatment solution, an oxidized metal powder is added to the treatment solution to obtain an anhydrous ethanol-hydrogen peroxide-oxidized metal mixed solution, carbon nanotubes are added to the anhydrous ethanol-hydrogen peroxide-oxidized metal mixed solution, and then ultrasonic, centrifugal, and drying treatments are performed to separate the pre-branched carbon nanotubes; S2: The pre-branched carbon nanotubes obtained in S1 are immersed in a chitosan aqueous solution, and the modified carbon nanotubes are obtained after magnetic stirring, centrifugation and drying.

3. The sulfate-resistant concrete according to claim 2, characterized in that: The mass ratio of the metal oxide powder to the treatment liquid in S1 is 1:(3-5).

Citation Information

Patent Citations

  • A method for preparing and applying a highly efficient sulfate ion adsorption material

    CN102258984A

  • Graphene loaded zirconium oxide composite material, preparing method thereof, and application thereof as desulfurizer adsorbent

    CN106000297A

  • Carbon nanotube concrete and preparation method thereof

    CN113880525A